Risk Factors Related to Operative Duration and Their Relationship With Clinical Outcomes in Pediatric Patients Undergoing Roux-en-Y Hepaticojejunostomy - Zhou, Yongjun; Zhang, Yunfei; Guo, Hongjie; Zheng, Chao; Guo, Chunbao (Frontiers in Pediatrics, 2020)
Background: Operative duration might be important for perioperative morbidity, and its involvement has not been fully characterized in paediatric patients. We determined perioperative variables in association with operative duration and their influence on clinical outcomes in paediatric patients. Methods: We retrospectively reviewed 701 patients who underwent elective removal of choledochal cysts followed by Roux-en-Y hepaticojejunostomy. The patients were separated into the long-time group (>165 min) and short-time group (<165 min) based on median operating time (165 min). Propensity score matching was performed to adjust for any potential selection bias. The independent risk factors for operative time were determined using multivariable logistic regression analyses. Results: The operating time was often increased by excision difficulty caused by a larger choledochal cyst size (OR=1.56; 95% CI, 1.09–2.23; p<0.001), a greater BMI (OR=1.02; 95% CI, 1.00–1.15; p=0.018), and older age (OR=1.17; 95% CI, 1.02–1.39; p=0.012) in multivariate analysis. Long-time surgical duration was associated with delayed gastrointestinal functional recovery, measured using the time to first defecation (p=0.027) and first bowel movement (p=0.019). Significantly lower levels of serum albumin were found in the long-time group than in the short-time group (p=0.0035). The total length of postoperative hospital stay was longer in patients in the long-time group (7.51±2.03 days) than those in the short-time group (6.72±1.54 days, p = 0.006). Conclusions: Our data demonstrated that short operating time was associated with favourable postoperative results. The influencing factors for operating time should be ameliorated to achieve better outcomes.